2019
DOI: 10.1186/s12871-019-0744-4
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of pleth variability index in predicting preload responsiveness of mechanically ventilated patients under various conditions: a systematic review and meta-analysis

Abstract: Background Goal-directed volume expansion is increasingly used for fluid management in mechanically ventilated patients. The Pleth Variability Index (PVI) has been shown to reliably predict preload responsiveness; however, a lot of research on PVI has been published recently, and update of the meta-analysis needs to be completed. Methods We searched PUBMED, EMBASE, Cochrane Library, Web of Science (updated to November 7, 2018) and the associated references. Relevant aut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Furthermore, in this study, PI LRM had better ability to indicate fluid responders than PVI at baseline. This finding is similar to that of a previous meta-analysis (39), which reported that PVI reliability to predict fluid responsiveness in surgical patients under mechanical ventilators might be reduced. Nevertheless, further studies should be performed to validate these findings.…”
Section: Correlation Of Pi Lrm Pvi Pi and Ppv T1 With Changes In Svsupporting
confidence: 91%
“…Furthermore, in this study, PI LRM had better ability to indicate fluid responders than PVI at baseline. This finding is similar to that of a previous meta-analysis (39), which reported that PVI reliability to predict fluid responsiveness in surgical patients under mechanical ventilators might be reduced. Nevertheless, further studies should be performed to validate these findings.…”
Section: Correlation Of Pi Lrm Pvi Pi and Ppv T1 With Changes In Svsupporting
confidence: 91%
“…PPV is an index for evaluating the volume status of patients undergoing mechanical ventilation under general anesthesia and judging their volume responsiveness based on the mechanism of the cardiopulmonary interaction. It is a dynamic index and has recently been viewed for the commonly used indicators of anesthesia volume management 24,25 . Renner et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis by Liu et al highlighted the wide range of PVI cut-off value (from 7% to 20%), depending on the studied population and ventilation settings (e.g., ICU, or, tidal volume, positive end expiratory pressure…) to predict fluid responsiveness [69].…”
Section: Pi Respiratory Variations and Prediction Of Fluid Responsivenessmentioning
confidence: 99%